The musculotendinous interface: insights into development, injury, and recovery for military medical applications - Adams, Alex T.; Davis, Zachary G.; Browder, Kyle F.; Dearth, Christopher L.; Goldman, Stephen M. (Frontiers in Physiology, 2025)
Musculoskeletal injuries (MSKIs) are a major cause of morbidity and lost duty time for military service members, impacting overall military readiness, with overuse injuries being particularly prevalent among them. Musculotendinous injuries, affecting the musculotendinous unit, are especially problematic due to their long recovery times and limited treatment options. To better understand these injuries, this review delves into the developmental, homeostatic, and structural biology of musculotendinous units, with a focus on the musculotendinous junction (MTJ). Additionally, it explores the biomechanical model of the musculotendinous unit and the complexities of endogenous repair processes for muscle, tendon, and MTJ injuries. Based on these insights, the review discusses promising therapeutic approaches for treating these injuries, such as anabolic agents, metabolic reprogramming, scaffold or cell-based therapies, and physical therapy. These emerging therapies offer potential avenues for accelerating endogenous healing, reducing recovery time, and improving long-term outcomes for musculotendinous injuries. Ultimately, further research in this area could significantly enhance military readiness by mitigating the impact of MSKIs on service members.